2019
DOI: 10.1051/ject/201951078
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Venous Drainage and the 3/8-Inch Venous Line: What Would Poiseuille Do?

Abstract: The 1/2″ venous line has long been the drainage tubing diameter of choice for adult patients undergoing cardiac surgery. However, several programs use a smaller diameter venous line when used in conjunction with kinetic-assisted venous drainage or vacuum-assisted venous drainage. In 2014, our perfusion team made an institution-wide effort to miniaturize the cardiopulmonary bypass (CPB) circuit for children. One of our changes was the transition to a 3/8″ diameter venous line for drainage, even in our larger pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…A study effectively demonstrated this principle by reducing priming volume, transitioning from a ½" to a 3/8" venous line, and compensating for the diameter reduction by shortening the tube's length, thereby maintaining optimal venous drainage. Given that blood viscosity typically remains within physiological limits during bypass, finetuning the diameter and length of the tubing can optimize venous return in a bypass circuit [8,9].…”
Section: Cardiopulmonary Bypass and Venous Dynamicsmentioning
confidence: 99%
“…A study effectively demonstrated this principle by reducing priming volume, transitioning from a ½" to a 3/8" venous line, and compensating for the diameter reduction by shortening the tube's length, thereby maintaining optimal venous drainage. Given that blood viscosity typically remains within physiological limits during bypass, finetuning the diameter and length of the tubing can optimize venous return in a bypass circuit [8,9].…”
Section: Cardiopulmonary Bypass and Venous Dynamicsmentioning
confidence: 99%